Enhanced thermoelectric performance in Cl-doped BiSbSe3 with optimal carrier concentration and effective mass. (20th April 2021) - Wang, Sining; Su, Lizhong; Qiu, Yuting; Xiao, Yu; Zhao, Li-Dong
Abstract: Possessing inherently low thermal conductivity, BiSbSe3 is a promising thermoelectric material for medium temperature. Therefore, to substantially optimize the thermoelectric performance of BiSbSe3, researchers mainly focus on the strategies to improve its electrical transport properties. Among these strongly coupled thermoelectric parameters, carrier concentration and effective mass are two intrinsic variables to decisively affect the electrical transport properties. In this work, Cl as a donor dopant is effective to provide extra electrons in n -type BiSbSe3, and the carrier concentration and effective mass can be well optimized simultaneously with increasing Cl content owing to the multiple conduction bands in BiSbSe3 . What's more, maximum weighted mobility ∼53 cm 2 V −1 s −1 is obtained in Cl-doped BiSbSe3, which contributes to a largely enhanced power factor ∼4.8 μW cm −1 K -2 at room temperature and outperforms other halogen-doped BiSbSe3 samples. Finally, combining the significantly enhanced power factor and maintained low thermal conductivity, a maximum ZT ∼1.0 is achieved in Cl-doped BiSbSe3 at 800 K.